Total Reconstitution of Functionally Active 50S Ribosomal Subunits from Escherichia coli - Nierhaus, Knud H. (1974)
Total reconstitution of 50S subunits from E. coli was achieved by a two-step incubation procedure. In the first step, 23S RNA, 5S RNA, and the total proteins from 50S subunits were incubated for 20 min at 40° in the presence of 4 mM Mg(++) and 400 mM NH(4)Cl. In the second step, the Mg(++) concentration was raised to 20 mM and the incubation was performed for 90 min at 50°. No requirement for 30S subunits or other components (e.g., polyamine) was found. The reconstituted particle has the same sedimentation coefficient as the native 50S subunit and is highly active in protein synthesis with natural (R17 RNA) and artificial [poly(U)] messengers as well as in tests for peptidyltransferase (fragment assay) and for binding of antibiotics (chloramphenicol).